Antecedents of mobile marketing adoption by SMEs:Does industry variance matter?. Issue 3 (3rd July 2021) - Maduku, Daniel K.
ABSTRACT: Although innovations such as mobile marketing offer targeting and a cost-effective approach to marketing that could be leveraged by small and medium-sized enterprises (SMEs), most SMEs have shown a noticeable skepticism toward adopting the innovation. To overcome this adoption inertia, more research is necessary. This study draws on an integrated framework with theoretical considerations from the technology–organization–environment (TOE) framework to examine how factors in the technology context (relative advantage, complexity, and compatibility), the organizational context (top management support, financial resource slack, and employee mobile marketing capability) and the environmental context (mobile marketing vendor support, competitive pressure, and customer pressure) predict marketing adoption behavior by South African SMEs. Using a comparative analysis, the study further ascertains whether industry variance moderates the factors predicting mobile marketing adoption behavior between manufacturing and tourism-sector SMEs. Data for the empirical testing of the integrated framework were randomly sourced from 201 SMEs in the manufacturing and tourism sectors. The results show that relative advantage, complexity, top management support, competitive pressure, and vendor support are key drivers of mobile marketing adoption in the overall sample of manufacturing and tourism sector SMEs in South Africa. However, the results not only show different set predictors of mobile marketing adoption between the manufacturing and tourism sector SMEs: they also emphasize that the relative importance of the salient determinants of the innovation's adoption varies across the industries, suggesting that industry variance plays a significant moderating role in mobile marketing adoption decisions across the two SME sectors that are examined. The implications of the findings for researchers and practitioners interested in promoting a more favorably disposed adoption of mobile marketing at the SME interface are discussed.